2019
DOI: 10.1021/acschembio.9b00462
|View full text |Cite
|
Sign up to set email alerts
|

DPP9’s Enzymatic Activity and Not Its Binding to CARD8 Inhibits Inflammasome Activation

Abstract: Inflammasomes are multiprotein complexes formed in response to pathogens. NLRP1 and CARD8 are related proteins that form inflammasomes, but the pathogen-associated signal(s) and the molecular mechanisms controlling their activation have not been established. Inhibitors of the serine dipeptidyl peptidases DPP8 and DPP9 (DPP8/9) activate both NLRP1 and CARD8. Interestingly, DPP9 binds directly to NLRP1 and CARD8, and this interaction may contribute to the inhibition of NLRP1. Here, we use activity-based probes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(124 citation statements)
references
References 31 publications
15
109
0
Order By: Relevance
“…4d, e). These results are broadly consistent with previous results demonstrating that hDPP9 S759A failed to fully rescue hNLRP1 activation in hDPP9-deficient 293T cells 8 . DPP8/9 inhibitors like VbP have been shown to bind to the active site of hDPP9, which overlaps with the UPA-binding site.…”
Section: Role Of the Dpp9 Catalytic Activity And Dpp9-fiind Interactisupporting
confidence: 93%
See 3 more Smart Citations
“…4d, e). These results are broadly consistent with previous results demonstrating that hDPP9 S759A failed to fully rescue hNLRP1 activation in hDPP9-deficient 293T cells 8 . DPP8/9 inhibitors like VbP have been shown to bind to the active site of hDPP9, which overlaps with the UPA-binding site.…”
Section: Role Of the Dpp9 Catalytic Activity And Dpp9-fiind Interactisupporting
confidence: 93%
“…To probe the mechanism of NLRP1 inhibition by DPP9, we co-expressed fulllength rNLRP1 and rDPP9 in insect cells and purified them using affinity chromatography. Supporting previous studies 3,8,9 , gel filtration analysis indicated that the two proteins formed a stable complex (Extended Data Fig. 2a).…”
Section: Architecture Of the 2:1 Rnlrp1-rdpp9 Complexsupporting
confidence: 84%
See 2 more Smart Citations
“…Notably, DPP9 (as well as DPP8) was recently discovered to directly bind the FIINDs of both hNLRP1 and CARD8. 62,68 The catalytic activity of DPP9 was not required for these interactions, as the catalytically dead S759A mutant DPP9 still bound to both hNLRP1 and CARD8. Despite these similarities, however, the hNLRP1-DPP9 and CARD8-DPP9 interactions appear to be remarkably distinct (Table 2).…”
Section: The D Ipep Tidyl Pep Tida S E S 8 and 9 (D Pp8/9)mentioning
confidence: 99%